Notions of Temporalities in Artistic Practice - Batista, Anamarija (De Gruyter, 2022)
This publication focuses on the ideas of temporality in artistic practices. The analysis and reflection of various approaches enable the reader to delve into situation-specific settings and to contextualize and examine the question of how temporality initiates action and structures of perception, weaves itself into these structures, and thereby affects our bodies, our senses, our communication and shapes our presence.